PENGARUH BIOGRAFIS DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING STUDI PADA BMT BINAAN PINBUK TULUNGAGUNG - Albanjari, Fatkhur R. (UIN Sayyid Ali Rahmatullah Tulungagung, 2016)
The research aims to know the influence of biographical characteristics and leadership to performance of employee through motivation as an intervening variable. This study is on BMT’s supervised by Pinbuk Tulungagung. The taken samples in this study were 50 respondents from 7 BMT’s registered in Pinbuk Tulungagung. The Sampling uses a non probability sampling with the technic of quota sampling. The measurements in this study use a scale of Likert. The used data analysis method is a path analysis with SPSS 20th version to test the effect of intervening variable. The results show that the biographical characteristics do not influence in the motivation; the leadership influences positively in the motivation; the biographical characteristics do not influence in the performance of employees; the leadership influences positively and significantly in the performance of employees; and the motivation influences positively and statistically in performance of employees The result of path analysis shows that biographical characteristics do not influence in the performance of employees through motivation; and the leadership influences significantly and positively in the performance of employees through motivation.Keywords: Biographical Characteristics, Leadership, Motivation.